2019
DOI: 10.1111/1460-6984.12473
|View full text |Cite
|
Sign up to set email alerts
|

Verb‐mediated anticipatory eye movements in people with Down syndrome

Abstract: Background: Children and adults with neurotypical development employ linguistic information to predict and anticipate information. Individuals with Down syndrome (DS) have weaknesses in language production and the domain of grammar but relative strengths in language comprehension and the domain of semantics. What is not clear is the extent to which they can use linguistic information, as it unfolds in real time, to anticipate upcoming information correctly. Aims: To investigate whether children and young peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…We also found that mental age influences prediction in people with DS in an unexpected direction: participants with DS with greater mental age looked less at the target in the MV condition. This result is contrary to that of Arias-Trejo et al (2019) , who found a positive correlation between mental age and the predictive ability of people with DS. Differences in the mental age evaluation might explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We also found that mental age influences prediction in people with DS in an unexpected direction: participants with DS with greater mental age looked less at the target in the MV condition. This result is contrary to that of Arias-Trejo et al (2019) , who found a positive correlation between mental age and the predictive ability of people with DS. Differences in the mental age evaluation might explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Differences in the mental age evaluation might explain this discrepancy. Arias-Trejo et al (2019) computed mental age by evaluating verbal and non-verbal cognitive domains. In the present study, mental age was based on comprehension ability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations